2017
DOI: 10.5935/abc.20170112
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and Reliability Of QTc and QTcd Measurements and Their Relationships with Left Ventricular Hypertrophy in Hemodialysis Patients

Abstract: BackgroundLeft ventricular hypertrophy (LVH) is very common in hemodialysis patients and an independent risk factor for mortality in this population. The myocardial remodeling underlying the LVH can affect ventricular repolarization causing abnormalities in QT interval.Objectiveto evaluate the reproducibility and reliability of measurements of corrected QT interval (QTc) and its dispersion (QTcd) and correlate these parameters with LVH in hemodialysis patients.MethodsCase-control study involving hemodialysis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Increased QTcd reflects the presence of complex repolarization patterns, especially a certain degree of fusion of the T and U waves, which may characterize various proarrhythmic conditions better than QT/QTc duration 41,42 . This is possibly due to the fact that QT (or QTc) duration is vulnerable to intrinsic and extrinsic factors, such as myocardium characteristics and changes, cell death, biochemical alterations, and disturbances in neurohormonal regulation, unlike dispersion of QTc 43,44 . Moreover, prolonged QT may sometimes be associated with inherited long QT syndromes 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased QTcd reflects the presence of complex repolarization patterns, especially a certain degree of fusion of the T and U waves, which may characterize various proarrhythmic conditions better than QT/QTc duration 41,42 . This is possibly due to the fact that QT (or QTc) duration is vulnerable to intrinsic and extrinsic factors, such as myocardium characteristics and changes, cell death, biochemical alterations, and disturbances in neurohormonal regulation, unlike dispersion of QTc 43,44 . Moreover, prolonged QT may sometimes be associated with inherited long QT syndromes 43 .…”
Section: Discussionmentioning
confidence: 99%
“…41,42 This is possibly due to the fact that QT (or QTc) duration is vulnerable to intrinsic and extrinsic factors, such as myocardium characteristics and changes, cell death, biochemical alterations, and disturbances in neurohormonal regulation, unlike dispersion of QTc. 43,44 Moreover, prolonged QT may sometimes be associated with inherited long QT syndromes. 43 Therefore, it has been reported that, compared with QTc prolongation, increased dispersion of QT/QTc was a more powerful predictor of susceptibility to ventricular tachyarrhythmias, suggesting that lack of homogeneity of repolarization is more closely associated with arrhythmic risk than is the prolongation of repolarization itself.…”
Section: Discussionmentioning
confidence: 99%
“…Among HD-dependent patients, longer QTc intervals are associated with thicker left posterior ventricular walls as the utmost marker of mortality. 19 However, we did have any such echocardiographic information available for our patients.…”
Section: Discussionmentioning
confidence: 99%
“…We read the publication on "QTc and QTcd Measurements and Their Relationships with Left Ventricular Hypertrophy in Hemodialysis Patients", which is very interesting. 1 Alonso et al 1 concluded that "We found that QTc interval, in contrast to QTcd, is a reproducible and reliable measure and had a weak but positive correlation with LVMi in HD patients." This report used an unmatched control group; hence, the selection bias can be expected.…”
mentioning
confidence: 90%